Dialektyka solidarności a państwo prawa - Kaleta, Krzysztof J. (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The article concerns the significance of the idea of solidarity for the rule of law within contemporary constitutional democracies. The author presents, with reference to P. Ricouer’s philosophy, the dialectical nature of solidarity which mediatises ideals of love and justice. He also presents the solidarity’s place within liberal and republican political thought. The author points the limitations imposed on the idea of solidarity by the model of liberal constitutionalism. At the same time he emphasises that legal recognition related to liberal culture of human rights gains its social complement in the idea of solidarity. He argues that the idea of solidarity might determine the concept of legitimization of power in its modern formula. The idea of solidarity and the concept of rule of law both realise – in different ways and on different levels – the common values oriented towards elimination of arbitrariness of power and ensuring conditions for cooperation between members of political community. The constitutional justice may perform a leading role in fulfilment the idea of solidarity as it watches over distribution of political power and secures processes of free communication within political community.